Growth and Survival Rate of Redclaw Crayfish Cherax quadricarinatus Reared with Different Density in Recirculation System - Tatag Budiardi; D Y Irawan; Dinamella Wahjuningrum (Jurnal Akuakultur Indonesia)
The objective of this research was to know the growth and survival rate of redclaw crayfish (Cherax quadricarinatus) reared in recirculation system with density 20, 30, 40 and 50 m-2. Lobster with 6.02 ± 0.13 cm length and 6.23 ± 0.51 gram initial body weights were cultured in 60 x 30 x 40 cm aquarium and compiled in recirculation system, for 42 days. Result of research showed that there are statistically difference at growth rate daily weight, coefficient of variances and feed efficiency (p0.05). From this research it can be concluded that the best density for freshwater crayfish (Cherax quadricarinatus) was 50 m-2.